2016
DOI: 10.17116/profmed20161934-11
|View full text |Cite
|
Sign up to set email alerts
|

Detection of malignant tumors of the breast and female reproductive organs during medical prophylactic examination of certain adult population groups

Abstract: 1 Московский научно-исследовательский онкологический институт им. П.А. Герцена -филиал ФГБУ «национальный медицинский исследовательский радиологический центр» Минздрава россии, Москва, россия; 2 ФГБУ «национальный медицинский исследовательский радиологический центр» Минздрава россии, обнинск, россия; 3 ФГБУ «Государственный научно-исследователь-ский центр профилактической медицины» Минздрава россии, Москва, россия Цель исследования -анализ эффективности диспансеризации определенных групп взрослого населения ро… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
2
1
0
3
Order By: Relevance
“…Discussion. The results of the study demonstrated that BrCa incidence in the cohort of female nuclear workers employed at the Mayak PA was associated with many nonradiation factors and the results were mostly in line with those obtained in other studies [2,5,6,8,12,[14][15][16][17][18][19][20][21][22]32].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Discussion. The results of the study demonstrated that BrCa incidence in the cohort of female nuclear workers employed at the Mayak PA was associated with many nonradiation factors and the results were mostly in line with those obtained in other studies [2,5,6,8,12,[14][15][16][17][18][19][20][21][22]32].…”
supporting
confidence: 87%
“…BrCa is a multifactorial disease. There are several established factors that cause elevated risks of BrCa including age older than 40 years, early menarche (before 12 years of age), late menopause (at age 55 years and later), the first pregnancy terminated by abortion, infertility, age at first birth (30 years and later), breast feeding, reproductive losses, proliferative changes in breast tissues, BrCa in health history of immediate relatives, education, height, body mass index, smoking and some others [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…Установленными (доказанными) факторами, повышаю-щими риск развития РМЖ, являются: возраст старше 40 лет, раннее менархе (до 12 лет), поздняя менопауза (после 55 лет), аборт при первой беременности, бесплодие, возраст первых родов (старше 30 лет), кормление грудью, репродуктивные потери, пролиферативные изменения в молочных железах (МЖ), наличие РМЖ у ближайших родственников, образование, рост, индекс массы тела, курение и др. [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
unclassified
“…Результаты проведенного исследования показали, что заболеваемость РМЖ в когорте работниц предприятия атомной промышленности ПО «Маяк» зависит от большого количества нерадиационных факторов, что в основном хорошо согласуется с данными других исследований [2,5,6,8,12,[14][15][16][17][18][19][20][21][22]32]. Например, риск заболеваемости РМЖ ожидаемо воз-растал с увеличением достигнутого возраста [2,5,6], как и во многих других исследованиях.…”
unclassified
See 1 more Smart Citation